Ontology At Work: Constructing the Learner/Worker - David Beckett; Gayle Morris (Adult Education Research Conference, 2000)
Constructing adult learners’ and workers’ identities starts with their embodied actions, and to do this we present a philosophical perspective, two fieldwork sites and a model for learning.